Dynamics of the incorporation of Co into the wurtzite ZnO matrix and its magnetic properties - Mesquita, A. [UNESP]; Rhodes, F. P.; Da Silva, R. T.; Neves, P. P.; De Zevallos, A. O.; Andreeta, M. R.B.; De Lima, M. M.; Cantarero, A.; Da Silva, I. S.; Boselli, M. A.; Gratens, X.; Chitta, V. A.; et al. (Elsevier, 2015)
Abstract Bulk Co-doped ZnO (Zn1-xCoxO) samples were prepared and studied with particular emphasis on their compositions, structures, and magnetic properties. A detailed microstructural analysis was conducted to investigate the nature of Co incorporation into the wurtzite ZnO matrix. The Zn1-xCoxO ceramic samples were prepared using the standard solid-state reaction method with different Co molar concentrations of up to 30%. A Co solubility limit of approximately 23% was determined. For samples with Co concentrations greater than 23%, a segregated phase identified as Zn-doped CoO (Co1-yZnyO with y = 0.23) was observed. The magnetic characterization for the single-phase samples revealed a paramagnetic behavior with antiferromagnetic coupling of Co2+ ions within the ZnO matrix. In order to get more insight about the magnetic results Monte Carlo simulations were conducted for different magnetic couplings and different Co distributions over the volume of the samples. We discussed the observed magnetic behavior of our samples by considering the main theories regarding the magnetic properties of dilute magnetic oxides. An inhomogeneous distribution of Co ions within the grains was inferred from the microstructural and magnetic characterization.
Keywords: Co distribution; Dilute magnetic oxide; Magnetic properties; Phase diagram; Spintronic; Zn1-xCoxO